P024: Extracurricular podcast use behaviour and effect on knowledge retention in undergraduate medical students. (2nd June 2016) - Chin, A.; Helman, A.; Chan, T.M.
Abstract : Introduction: Podcasts have become increasingly popular as a medium for free online access medical education (FOAM). However, little research has examined the naturalistic use of podcasts as a tool in undergraduate medical education. This study aims to determine usage conditions, preferences, and level of retention of information from podcasts by medical students at a Canadian University.Methods: Medical students (Years 1 to 3) were instructed to complete an online test assessing their baseline knowledge on the topics of the podcasts and for qualitative data on podcast usage and preferences. Audio podcasts on two topics (adult asthma, and introduction to toxicology) were then distributed to study participants. One week and two weeks after the initial survey students were asked to complete a follow-up survey for knowledge assessment and further podcast usage data. Simple descriptive statistical generated using Microsoft Excel. Paired samples t-tests were utilized to assess knowledge acquisition using Microsoft SPSS version 23.Results: Participants who successfully completed the knowledge assessments demonstrated a significant effect of learning (Asthma, average test score improvement of 30%, p=0.002; Toxicology, average test score improvement of 13%, p=0.004). The majority of participants who stated a preference in podcast length indicated they preferred podcasts of 30 or less minutes (85%). The top three activities participants were engaged in while listening to the podcasts were driving (46%), completing chores (26%), and exercising (23%). A large number of participants who did not complete the study in its entirety cited a lack of time and podcast length to be the top two barriers to completion.Conclusion: This is one of the first studies to examine podcast usage data and preferences in a Canadian undergraduate medical student population. This information may help educators and FOAM producers to optimize educational tools for medical education.